2019
DOI: 10.3390/molecules24183220
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Ophiopogonis Radix from Two Different Producing Areas

Abstract: Ophiopogonis Radix, also known as Mai-dong in Chinese, was a commonly used traditional Chinese medicine (TCM) and functional health food. Two products of Ophiopogonis Radix are largely produced in the Sichuan and Zhejiang province, which are called “Chuan maidong (CMD)” and “Zhe maidong (ZMD)” respectively. To distinguish and evaluate the quality of CMD and ZMD, an analytical method based on ultra-fast performance liquid chromatography coupled with triple quadrupole-linear ion trap mass spectrometry (UFLC-QTRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In order to evaluate the content difference of 22 constituents in xylem and phloem, t-test analysis was used and the values of p less than 0.05 were considered remarkably different [20,21]. As illustrated in Figure 6, more than half of the bioactive constituents investigated in this study showed significant difference between xylem and phloem.…”
Section: T-test Of Samplesmentioning
confidence: 94%
See 2 more Smart Citations
“…In order to evaluate the content difference of 22 constituents in xylem and phloem, t-test analysis was used and the values of p less than 0.05 were considered remarkably different [20,21]. As illustrated in Figure 6, more than half of the bioactive constituents investigated in this study showed significant difference between xylem and phloem.…”
Section: T-test Of Samplesmentioning
confidence: 94%
“…The standards of procyanidin B2 (5), daidzin (7), dihydroquercetin (8), genistin (9), liquiritigenin (12), calycosin (14), naringenin (15), genistein (16), medicarpin (20), prunetin (21) and biochanin A (22) were purchased from Nanjing Liangwei biotechnology Co., Ltd. (Nanjing, China). Epicatechin (6), rutin (10), kaempferol (17) and formononetin (19) were purchased from the Chinese National Institute for the Control of Pharmaceutical and Biological Products (Beijing, China).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also enables the simultaneous determination of multiple compounds, which greatly shortens analysis time [27]. In summary, this technique possesses remarkable superiority in selectivity, sensitivity, and analysis capability, so it has been widely used for the separation and analysis of metabolites in medicinal materials [28][29][30]. Herein, the UFLC-QTRAP-MS/MS technology was adopted for the simultaneous determination of twenty-one analytes in FF.…”
Section: Selection Of Determination Methodsmentioning
confidence: 99%
“…Tan M.X. et al[29] applied ultra-fast performance liquid chromatography coupled with triple quadrupole-linear ion trap mass spectrometry (UFLC-QTRAP-MS/MS) to measure 36 components of Ophiopogonis Radix and found the bioactive constituents in Ophiopogonis Radix from different regions were signi cantly different; Shu Z. et al[30] employed reversed-phase high-performance liquid chromatography coupled with hierarchical clustering analysis to evaluate the quality of Vitex negundo seeds, and observed signi cant differences in the content of lignans of Vitex negundo seeds from different origins; Cao Y. et al[31] in order to evaluate the quality consistency of Chansu, established HPLC ngerprints of Chansu and discovered that the ngerprint pro le of Chansu from different geographical origins were different.…”
mentioning
confidence: 99%